Atrial natriuretic factor in normal subjects and heart failure patients. Plasma levels and renal, hormonal, and hemodynamic responses to peptide infusion. - Cody, R J (1986)
We investigated atrial natriuretic factor (ANF) in humans, measuring plasma immunoreactive (ir) ANF (in femtomoles per milliliter), and renal, hormonal, and hemodynamic responses to ANF infusion, in normal subjects (NL) and congestive heart failure patients (CHF). Plasma irANF was 11 +/- 0.9 fmol/ml in NL and 71 +/- 9.9 in CHF (P less than 0.01); the latter with twofold right ventricular increment (P less than 0.05). In NL, ANF infusion of 0.10 microgram/kg per min (40 pmol/kg per min) induced increases (P less than 0.05) of absolute (from 160 +/- 23 to 725 +/- 198 mueq/min) and fractional (1-4%) sodium excretion, urine flow rate (from 10 +/- 1.6 to 20 +/- 2.6 ml/min), osmolar (from 3.2 +/- 0.6 to 6.8 +/- 1.2 ml/min) and free water (from 6.8 +/- 1.6 to 13.6 +/- 1.6 ml/min) clearances, and filtration fraction (from 20 +/- 1 to 26 +/- 2%). Plasma renin and aldosterone decreased 33% and 40%, respectively (P less than 0.01). Systolic blood pressure fell (from 112 +/- 3 to 104 +/- 5 mmHg, P less than 0.05) in seated NL; but in supine NL, the only hemodynamic response was decreased pulmonary wedge pressure (from 11 +/- 1 to 7 +/- 1 mmHg, P less than 0.05). In CHF, ANF induced changes in aldosterone and pulmonary wedge pressure, cardiac index, and systemic vascular resistance (all P less than 0.05); however, responses of renin and renal excretion were attenuated. ANF infusion increased hematocrit and serum protein concentration by 5-7% in NL (P less than 0.05) but not in CHF.